Using Case Study Methodology to Approach the Views of Teachers of English on Classroom Disciplinary Strategies - Claudio Díaz Larenas (Universidad Nacional de Colombia, 2012)
This qualitative study aims at identifying the disciplinary strategies claimed to be used by a group of five secondary classroom teachers of English in public or semi-public schools in Chile. To conduct this research, a semi-structured interview was applied to participants. The data were analyzed using the principles of semantic content analysis and the grounded theory technique in order to organize the categories and subcategories from the data. The results show that some of the teachers declare using a rising tone of voice, scolding and expelling difficult students from the classroom as key disciplinary techniques; other teachers claim that disciplinary strategies help them to accomplish the teaching aim in a lesson.